2005
DOI: 10.1007/s00401-005-1000-1
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutations in glioblastoma multiforme

Abstract: Glioblastoma multiforme WHO grade IV is the most common and malignant variant of astrocytic tumors. Loss of heterozygosity of chromosome 10 and mutations in the tumor suppressor gene PTEN on 10q are molecular hallmarks of glioblastomas. Recently, mutations were identified in PIK3CA, encoding a protein that antagonizes the function of PTEN protein in the PI3K/Akt pathway. To address the question whether an exclusive mutation pattern can be observed in PIK3CA and PTEN, we determined the frequency of mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 11 publications
5
59
2
4
Order By: Relevance
“…In the current study, we investigated 10 exons of PIK3CA, previously shown to harbor mutations, by PCR amplification and direct DNA sequencing and found mutations in 11 of 73 (15%) samples. Several factors, which are discussed below, can account for the disparity between the current study and initial report of PIK3CA mutations in glioblastoma with mutation rates of 15% and 27%, respectively, and numerous other studies (3,(10)(11)(12) reporting a PIK3CA mutation rate of <7%.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…In the current study, we investigated 10 exons of PIK3CA, previously shown to harbor mutations, by PCR amplification and direct DNA sequencing and found mutations in 11 of 73 (15%) samples. Several factors, which are discussed below, can account for the disparity between the current study and initial report of PIK3CA mutations in glioblastoma with mutation rates of 15% and 27%, respectively, and numerous other studies (3,(10)(11)(12) reporting a PIK3CA mutation rate of <7%.…”
Section: Discussioncontrasting
confidence: 69%
“…Four additional mutations, G1357A, A3062G, G3129T, and C3139T, although described in other malignancies (2, 6), have not yet been reported in glioblastomas. The remaining mutations in exons 1, 9, and 20 have been described previously in glioblastomas (2,3,10). For each mutated sample, corresponding matched normal DNA, when available, was sequenced to verify that the mutation was somatic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study investigating all three genes that encode the catalytic subunits of PI3K (PIK3CA, PIK3CD and PIK3C2B) did not find PIK3CA mutations but did observe PIK3C2B amplification and PIK3CD mRNA overexpression in GBM (Knobbe and Reifenberger, 2003). Interestingly, PIK3CA and PTEN mutations have been observed to occur simultaneously in endometrial tumors and GBM indicating a potential additive effect of both mutations on pathway activation (Broderick et al, 2004;Oda et al, 2005;Hartmann et al, 2005a;Hayes et al, 2006). Intriguingly, 100% (five of five) of GBM with PIK3CA mutation also had 10q LOH (Hartmann et al, 2005a), suggesting the possibility that PTEN may be haploinsufficient when other mutations serve to upregulate signaling through the PI3K pathway, although the small number of tumors involved in this study do not allow a clear conclusion.…”
Section: Pi3k Pathway Involvement In Brain Tumorsmentioning
confidence: 99%